Determining factors of earnings management based on accrual model - Soliyah Wulandari; Asep Dadan Suganda (Jurnal Akuntansi dan Auditing Indonesia, 2021)
The research objective is to find empirical evidence of the factors influencing accruals earnings management in Jakarta Islamic Index Listed Companies which include company size, leverage, company age, profitability, and board directors. The population of the research is Jakarta Islamic Index Listed Companies. 13 samples were taken from these companies using the purposive sampling method and based upon the sample criteria. 71 observations were conducted on the 13 companies to obtain primary data of the research, while secondary data were collected through documentation of financial statement from Indonesia Stock Exchange. To test the research hypotheses, multiple regressions was used. The result of this research proved that company age and profitability have influence on accrual earnings management in Jakarta Islamic Index Listed Companies. On the other hand, company size, leverage, and board directors have no influence on accruals earnings management in Jakarta Islamic Index Listed Companies.